Aplikasi Kasir Mobile Berbasis Android Untuk Usaha Mikro Kecil Dan Menengah - Sari, Nova Noor Kamala; Purba, Fernata Firdaus (Journal of Information Technology and Computer Science, 2021)
Technology plays an important role in the management of a trading business, the cashier program at this time can be integrated with the Barcode Scanner which in its development is now implemented on smartphone cameras. The purpose of making this application is so that micro and small business owners can manage their business from product inventory to transaction processing with customers. The research method used to make this application begins with determining the scope of research, collecting data, consulting, studying literature, and implementing software development with the waterfall method. This application is based on Android so it uses the Java programming language with SQLite as the application database. It is hoped that this application can make it easier for micro and small business owners to advance their business.